De novo heterozygous pathogenic FBN1 variant in an autopsy case of multiple aneurysms and right renal artery dissection: a case report - MacGowan, Taylor; McClinchey, Taylor; Parcha, Vibhu; Vatta, Matteo; Litovsky, Silvio; Arora, Pankaj; Benson, Paul V. (Frontiers in Cardiovascular Medicine, 2023)
Background: Marfan syndrome is a potentially fatal inherited autosomal dominant condition impacting cardiovascular and skeletal system with an estimated 25% cases caused by sporadic genetic variations. Given the genetic inheritance pattern, autopsy of probands with Marfan syndrome associated mortality is critical to establish the phenotypic expression and clinical implications of the particular genetic variant, especially for first-degree relatives. We present the findings of a Marfan syndrome proband decedent presenting with sudden onset abdominal pain and unexplained retroperitoneal abdominal hemorrhage. Methods: An autopsy was performed to inform the blood relatives of the phenotypic expression and penetrance of the potentially heritable condition. CLIA-certified genetic sequencing was performed to identify pathogenic variants in genes associated with aortopathy. Results: Autopsy showed intra-abdominal and retroperitoneal hemorrhage due to infarction of the right kidney caused by dissection of the right renal artery. Genetic testing identified a heterozygous pathogenic FBN-1 gene variant 2953G>A (p.Gly985Arg). Conclusions: We report a case of previously undiagnosed Marfan syndrome death due to de novo mutation of the FBN-1 gene at c.2953G>A (p.Gly985Arg).